Dengue virus capsid protein binding to hepatic lipid droplets (LD) is potassium ion dependent and is mediated by LD surface proteins - Carvalho, Filomena A. (2012)
Universidade de Lisboa. Faculdade de Medicina. Instituto de Medicina Molecular. Lisboa, Portugal.